The changing face of paediatric airway endoscopic surgery: An 8-year single surgeon review. (May 2022) - Zubair, Arshad; Sutton, Liam; Murkin, Charlotte; Chioralia, Ana; Bajaj, Gaurav; Bajaj, Yogesh
Abstract: Introduction: As a recently established division, we sought to reflect on the development of our paediatric airway surgery service, and prospectively examine the diagnoses that underwent microlaryngobronchoscopy (MLB) to help quantify the evolving population demographics of paediatric airway disorders. Material and Methods: This was a prospective longitudinal study conducted of all paediatric MLBs performed by a single surgeon in a tertiary paediatric ENT centre between 2012 and 2019. Results: A total of 1040 MLBs were performed in 498 patients at the paediatric ENT centre of the Royal London Hospital. Median age at first procedure was 19 months. Median follow-up was 48 months. Primary diagnoses were laryngomalacia (21%), subglottic stenosis (SGS - 18%), laryngeal cleft (13%), and normal anatomy (28.3%). Repeat procedures were needed in 39.1% patients, who underwent a median of 2 repeat procedures. SGS (57.7%) constituted majority of the repeat category, followed by laryngeal cleft (12.36%), laryngomalacia (10.15%), unilateral/bilateral vocal cord palsy(4.24%) and laryngeal papilloma(4.24%). Laryngeal papilloma constituted largest number of procedures per patient (Median = 4, IQR = 5.75), followed by subglottic web and SGS. Mean length of stay(LOS) was 0.67 ± 0.96 days(d), with laryngeal cleft cases recording longest mean LOS. There was a steady increase in proportion of day-surgeries across study period [6.9% (2012) vs 59%(2019)]. Conclusion: SGS constitutes the major bulk of paediatric airway surgery, reflective of increasing number of premature births and prolonged intubation among neonates. Day-case MLB is a safe and feasible option in selected patients. This long-term data provides useful information to accurately prognosticate patients regarding potential number of repeat procedures for each diagnosis.